Effects of localized versus widespread TMD pain on sleep parameters in patients with bruxism: A single-night polysomnographic study - de Siqueira, José Tadeu Tesseroli; Camparis, Cinara Maria [UNESP]; de Siqueira, Silvia Regina Dowgan Tesseroli; Teixeira, Manoel Jacobsen; Bittencourt, Lia; Tufik, Sérgio (Elsevier, 2017)
Objective The purpose of this study was to investigate whether the presence of concomitant widespread pain could influence the polysomnographic characteristics of patients with Sleep Bruxism(SB) and chronic masticatory muscle pain(TMD). Methods 20 SB/TMD patients (17 women and 3 men) were evaluated according to the RDC/TMD questionnaire; and were divided into two groups according to the absence (Group A) or presence (Group B) of widespread pain. They were evaluated in a one night polysomnography paradigm. Results Group B had lower sleep efficiency (p = 0.034) and higher mean age (p = 0.000) than Group A. Self-reported orofacial pain complaints, clinical and emotional aspects (RDC/TMD Axis I and II), and SB PSG parameters were similar in both groups; all patients had masticatory myofascial pain and the pain characteristics were bilateral location (95.0%) and tightness/pressure quality (70.0%). Conclusions At a single-night PSG, SB/TMD patients with widespread pain presented lower PSG sleep efficiency and higher mean age.
Keywords: Myofascial pain; Orofacial pain; PSG; RDC/TMD questionnaire; Sleep bruxism; Temporomandibular disorders